Patterns of distress and psychosocial support 2 years post-displacement following a natural disaster in a lower middle income country - Nzayisenga, Emmanuel; Chan, Chim W.; Roome, Amanda B.; Therrien, Ann-Sophie; Sinclair, Isabelle; Taleo, George; Tarivonda, Len; Tosiro, Bev; Malanga, Max; Tagaro, Markleen; Obed, Jimmy; Iaruel, Jerry; et al. (Frontiers in Public Health, 2022)
Background: Displacement due to natural disaster exposure is a major source of distress, and disproportionately affects people in limited in low- and middle-income countries (LMICs). Public mental health resources following natural disasters and displacement are often limited in LMICs. In 2017, the population of one island in Vanuatu, a lower-middle income country, was displaced due to volcanic activity. Following the launch of a public mental health policy in 2009, psychosocial support interventions are increasingly available, providing an opportunity to assess relationships with distress following displacement. Methods: 440 people contributed data. We assessed distress using a local adaptation of the Impact of Events Scale-Revised, and types of psychosocial support available and received, including from health professionals, support groups, and traditional networks such as chiefs, traditional healers, and church leaders. We analyzed relationships between distress and psychosocial support, controlling for sociodemographic covariates. Results: Professional and group support was reported available by 86.8%-95.1% of participants. Traditional support networks were widely used, especially by men. Availability of professional support predicted lower distress among men (p<0.001) and women (p=0.015) (ηp2=0.026-0.083). Consulting church leaders for psychosocial support was associated with higher distress among men (p=0.026) and women (p=0.023) (ηp2=0.024-0.031). Use of professional and group support was lower than reported availability. Discussion: Increased collaboration between professional and traditional support networks could help respond to mental health needs following natural disasters in LMICs with limited infrastructure. Providing training and resources to church leaders might be a specific target for improvement. Promoting use of available services represents a continued public health need.